MEMPROGRAMKAN PENGENALAN MANAJEMEN SERTIFIKASI HALAL PADA DESA CIARUTEUN ILIR, KECAMATAN CIBUNGBULANG, BOGOR - Tubagus Rifqy Thantawi; Devi Andriani; Abdul Rohim (SAHID DEVELOPMENT JOURNAL, 2022)
This community service activity aims to provide knowledge and understanding about halalcertificates to the community, increase public awareness about the importance of halal certificatesand motivate people to have halal certificates for those who have businesses that are included inthe scope of halal products. Community service in programming the introduction of halalcertification management to the community of Ciaruteun Ilir Village, Cibungbulang District, Kab.Bogor, West Java. Service method Using the lesson study method. Basic knowledge of halal lawand high awareness of halal is not enough to guarantee the high desire of micro business actorsto take care of halal certificates. So far, the public has not received in-depth information regardingthe management procedures and costs of this halal certification. To increase the desire of businessactors to take care of certification, it is necessary to provide intensive assistance and financialassistance by the government.